A comparative study of food values between the United States and Norway. (22nd January 2018) - Bazzani, Claudia; Gustavsen, Geir W; Nayga, Rodolfo M; Rickertsen, Kyrre
Abstract: We compare the food values in the USA and Norway using the best–worst scaling approach. The food values examined are aimed at capturing the main issues related to food consumption such as naturalness, taste, price, safety, convenience, nutrition, novelty, origin, fairness, appearance, environmental impact and animal welfare. Results show that respondents in both countries have mostly similar food values, with safety being the most important value; while convenience and novelty are the least important values. Specifically, US respondents consider price more important and naturalness less important than Norwegian respondents.